Characteristic of no-synthase of peripheral blood lymphocytes of patients with rheumatic pathology - Efremova, Ulyana; Lychkovska, Nataliya; Fafula, Roman; Vorobets, Zinoviy (Journal of Medical Science, 2015)
It is known that NO is a ubiquitous mediator which acts as a universal modulator of various functions in organism and is produced by three isoforms of NO synthase. Nowadays the role of NO in the development of autoimmune diseases is actively studied. However, it remains unclear the biochemical and biophysical mechanisms of disturbances of NOS activity in blood lymphocytes at autoimmune process. The aim of present work is to study the kinetic properties of NO-synthase of peripheral blood lymphocytes of patients with rheumatic pathology. The study was carried out on peripheral blood lymphocytes isolated from patients with rheumatoid arthritis and ankylosing spondylitis. NOS activity was determined on the saponin-permeabilized blood lymphocytes. The difference between the values of NADPH oxidation with L-Arg and with inhibitor L-NAME reflects the value of the NADPH oxidation, ie total NOS activity. The kinetic properties of NO-synthase in peripheral blood lymphocytes of patients with rheumatic pathology were studied. It was found that the development of rheumatic pathology is associated with an imbalance in the NO synthesis and changes of kinetic parameters of NOS. It was shown that reduction in eNOS activity is accompanied by a sharp increase in activity of its inducible form. It was established that inhibition of eNOS occurs by noncompetitive type. NO production in lymphocytes of patients with rheumatic diseases is mainly realized by iNOS, whereas under normal physiological conditions endothelial form of the enzyme is being involved.